Risks of Artificial Intelligence-Based Decision Support and Decision-Making Systems in Executive-Level Decision-Making in Companies - A literature Review - Kappel, Gergely (Pécs journal of international and European law, 2025)
The study examines the risks associated with artificial intelligence (AI) based decision-making and decision-support systems in the decision-making processes of company executives, as well as small and medium-sized enterprises. Due to global trends and digital advancements, company management increasingly faces complex decisions, which AI-based decision-making and decision-support systems may well be suited to support. However, this carries several risks, and the study aims to identify the legal, ethical, and business risks associated with the use of such AI systems, with a particular focus on the decisions made by company executives. The analysis is based on a literature review, which will ultimately be compared with survey responses found in the AI Index Reports published annually by Stanford University.